Analysis of the activities that make up the reverse logistics processes and their importance for the future of logistics networks: An exploratory study using the topsis technique - Vitor William Batista Martins; Denilson Ricardo de Lucena Nunes; André Cristiano Silva Melo; Rayra Brand\~ao; Antônio Erlindo Braga Júnior; Verônica de Menezes Nascimento Nagata (Logistics, 2022)
Background: The wide variety of terms that converge in reverse logistics have been more evident and discussed in the current context of the literature, such as reverse channels, reverse supply chain, closed-loop supply chain, and circular supply chain. Regarding this, this paper aimed to investigate the level of uncertainty about the activities that make up the Reverse Logistics process in the opinion of professionals working in this area in Brazil, to develop a discussion relating to the sustainable development goals proposed by the UN and their importance for the future of logistics networks. Methods: Initially, through a detailed systematic review of the literature, the activities that make up the RL processes were identified. Then, a questionnaire was elaborated on regarding such activities, and a survey was developed with professionals in the area. The data obtained were analyzed through a descriptive analysis of means, calculation of Cronbach's Alpha, and using the multicriteria decision technique TOPSIS. Results: It is possible to see that professionals involved with RL processes in Brazil still have many doubts regarding which activities belong to the RL process. In the opinion of Brazilian professionals, 10 of these activities have generated high levels of uncertainties about their belonging or not to the RL process. On the other hand, with a low level of uncertainty, 3 activities were not considered and 3 were considered to make up the RL process. Conclusions: It is believed that this study can contribute to the generation of knowledge by comparing basic information in the scientific literature with the practical knowledge of professionals belonging to the reverse logistics sector working in the Brazilian context.
Keywords: 650; reverse logistics; reverse logistics activities; sustainable development; TOPSIS